Given,
`y = tanh^-1(x)+ ln(sqrt(1-x^2))`
so we have to find the y'
so,
`y' =(tanh^-1(x)+ ln(sqrt(1-x^2)))'`
`=(tanh^-1(x))'+(ln(sqrt(1-x^2)))'`
as we know
`(tanh^-1(x))' =1/(1-x^2)`
and so we have to find out
`(ln(sqrt(1-x^2)))' `
let `u =sqrt( 1-x^2)`
it can be solved by the following,
`(df)/dx = (df)/(du) * (du)/dx`
so,
`d/dx (ln(sqrt(1-x^2)))= d/(du) ln(u) * (du)/dx`
`= 1/u * d/dx (sqrt( 1-x^2))`
`=1/sqrt( 1-x^2) * (-x/sqrt( 1-x^2))`
`= -x/( 1-x^2)`
now,as
`y'=(tanh^-1(x)+ ln(sqrt(1-x^2)))'`
`=1/( 1-x^2) +(-x/( 1-x^2))`
`= (1-x)/( 1-x^2)`
`=1/(1+x)`
No comments:
Post a Comment